EFFECT OF ANTIGEN-PRIMED DENDRITIC CELL-BASED IMMUNOTHERAPY ON ANTITUMOR CELLULAR IMMUNE RESPONSE IN PATIENTS WITH COLORECTAL CANCER - V. V. Kurilin; E. V. Kulikova; A. V. Sokolov; Yu. A. Kozhevnikov; D. D. Blinova; I. A. Obleukhova; N. M. Starostina; S. V. Sennikov (Медицинская иммунология, 2021)
The problem of treatment of oncological diseases is one of the most urgent for modern medicine. Existing treatment approaches are based on a surgical, radiation, chemotherapeutic approach, and the use of immunotherapy methods aimed at markers and / or specific antigens of tumors.Approaches based on the mechanisms of cellular and molecular regulation of a specific antitumor immune response have shown their high efficiency (for example, antibodies against HER2 in breast cancer), but these approaches have a number of side and undesirable effects that limit their application. Considering the central role of the mechanisms of recognition of tumor antigens and their presentation to cytotoxic cells in effective tumor elimination, it is important to search for and develop approaches to restore these mechanisms in cancer pathology. Because maturation, differentiation of dendritic cells and their main function are impaired in oncological diseases, scientific research is underway to obtain mature dendritic cells and restore the natural way of antigen presentation to effector cells.The work carried out limited clinical studies (13 patients with colorectal cancer), a previously developed protocol for obtaining antigen-primed dendritic cells of patients with colorectal cancer and their joint culture with autologous mononuclear cells in vitro. From the peripheral blood of cancer patients, dendritic cells primed with autologous tumor antigens (tumor cell lysate), which were co-cultured with their own mononuclear cells in the presence of immunoregulatory cytokines (IL-12 and IL-18). The resulting cell suspensions were purified from the culture medium and cytokines and used for a course of immunotherapy (weekly, 20-30 million cells intravenously, dropwise), consisting of 3-5 injections. At different periods of immunotherapy (before the start of the course of immunotherapy, 3 months and 6 months after the end of immunotherapy), immunological parameters were assessed in the peripheral blood of patients (immunogram (CD3+, CD3+CD4+, CD3+CD8+, CD19, CD16+CD56+-cells), the relative content of T-regulatory cells (CD4+CD25+FoxP3+-cells), myeloid suppressor cells (CD14+HLA-DR- cells)) and assessed the cytotoxic activity of peripheral blood mononuclear cells of patients against cells of the tumor line of human colorectal cancer (Colo-320).The data obtained showed that in cancer patients, against the background of ongoing immunotherapy, the indicator of the direct cytotoxic test significantly increases, which makes it possible to judge the effective stimulation of the antitumor cellular immune response. This is also indicated by an increase in the relative number of CD16+CD56+-cells (NK-cells) 3 months after immunotherapy. The study of immunosuppressive cells in the blood of cancer patients showed the absence of significant changes in CD14+HLA-DR- -cells and T-regulatory cells.Thus, limited clinical studies of immunotherapy of patients with colorectal cancer based on autologous dendritic cells primed with lysate of autologous tumor cells demonstrated an increase in the antitumor cytotoxic immune response.